2010
DOI: 10.4049/jimmunol.0903174
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is Involved in Mycobacterium bovis Bacillus Calmette-Guérin–Activated Jagged1 and Notch1 Signaling

Abstract: Pathogenic mycobacteria have evolved unique strategies to survive within the hostile environment of macrophages. Modulation of key signaling cascades by NO, generated by the host during infection, assumes critical importance in overall cell-fate decisions. We show that NO is a critical factor in Mycobacterium bovis bacillus Calmette-Guérin–mediated Notch1 activation, as the generation of activated Notch1 or expression of Notch1 target genes matrix metalloproteinase-9 (MMP-9) or Hes1 was abrogated in macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 51 publications
0
36
0
1
Order By: Relevance
“…Activation of host signaling pathways upon engagement of surface-or intracellular-expressed PRRs is shown to dictate the immune cell fate. Contribution of signaling pathways like Sonic Hedgehog (30), WNT (31), and NOTCH (41,42) has been deciphered during various bacterial infections as well as during derailed inflammation (43)(44)(45). Here, we found significant contribution of WNT5A during dectin-1-mediated immune responses.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Activation of host signaling pathways upon engagement of surface-or intracellular-expressed PRRs is shown to dictate the immune cell fate. Contribution of signaling pathways like Sonic Hedgehog (30), WNT (31), and NOTCH (41,42) has been deciphered during various bacterial infections as well as during derailed inflammation (43)(44)(45). Here, we found significant contribution of WNT5A during dectin-1-mediated immune responses.…”
Section: Discussionmentioning
confidence: 60%
“…Our data clearly suggest the involvement of crucial kinases, like TAK1 and Pyk2, in mediating dectin-1-induced WNT5A-Ca 2ϩ / CAMKII signaling. NF-B, a unique transcription factor, is shown to regulate numerous immune cell functions under various pathological conditions (42,48). Regulation of NF-B nuclear translocation by TAK1 has been reported in T-cell-mediated functions (49).…”
Section: Discussionmentioning
confidence: 99%
“…Among the transcription factors, the active heterodimer p50/p65 forms of nuclear factor-B (NF-B) has been suggested to play a central role in immunological processes by inducing expression of a variety of genes involved in inflammatory responses (50,51,54,57,58). In this regard, Rv1917c triggered the activation of Akt as well as MAPKs, ERK1/2, and p38 MAPK (Fig.…”
Section: Rv1917c Skews Th1/th2 Balance Toward Th2 Ex Vivo-becausementioning
confidence: 99%
“…NO is found to play a role in TBM in mouse models, but there are few studies with human subjects. The role of NO has been established in disease processes over the years (14). It is shown that NO plays a role similar to cytokines in the disease process.…”
Section: Discussionmentioning
confidence: 99%